2012
DOI: 10.1016/j.jad.2011.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perinatal somatic and common mental disorder symptoms on functioning in Ethiopian women: The P-MaMiE population-based cohort study

Abstract: BackgroundLittle is known of the relationship between perinatal somatic and common mental disorder (CMD) symptoms and impaired functioning in women from settings where the burden of undernutrition and infectious disease morbidity is high.MethodsA population-based sample of 1065 women from Butajira, Ethiopia, was recruited in pregnancy (86.4% of those eligible) and reassessed two months postnatal (954 with singleton, live infants). At both time-points, women were administered a modified version of the Patient H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 40 publications
6
74
2
1
Order By: Relevance
“…In that study, a modified version of the PHQ-15 was implemented which: 1) eliminated two items regarding feeling tired/having low energy and problems sleeping based on an overlap with another study measure, and 2) modified item wording regarding menstruation to vaginal discharge. This study found the PHQ-15 predicted poorer daily functioning [21], providing initial evidence of suitability for use with perinatal women. However, the generalizability of these findings are limited to women in low-income countries when using a modified version of the PHQ-15.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…In that study, a modified version of the PHQ-15 was implemented which: 1) eliminated two items regarding feeling tired/having low energy and problems sleeping based on an overlap with another study measure, and 2) modified item wording regarding menstruation to vaginal discharge. This study found the PHQ-15 predicted poorer daily functioning [21], providing initial evidence of suitability for use with perinatal women. However, the generalizability of these findings are limited to women in low-income countries when using a modified version of the PHQ-15.…”
Section: Introductionmentioning
confidence: 53%
“…(p. 384) [20]. To our knowledge, only one prior study used the PHQ-15 with a perinatal sample and this was in a low-income country "where the burden of undernutrition and infectious disease morbidity is high (p. 340)" [21]. In that study, a modified version of the PHQ-15 was implemented which: 1) eliminated two items regarding feeling tired/having low energy and problems sleeping based on an overlap with another study measure, and 2) modified item wording regarding menstruation to vaginal discharge.…”
Section: Introductionmentioning
confidence: 99%
“…This version was used previously in the Butajira area [21, 22]. For this version, forward and backward translation was done by four research assistants who are fluent Amharic speakers, trained at masters’ degree level and had experience of translating, adapting and using mental health measures.…”
Section: Methodsmentioning
confidence: 99%
“…11 Notably, the prevalence of postpartum depression among women residing in high income countries is reported to be approximately 10% 12 and 20% for women in LAMICs. 3 The high prevalence of perinatal depression is influenced by a number of risk factors including increased somatic symptoms, 13 exposure to intimate partner violence, 14 lack of social support, 15 unintended pregnancy 16 and high rates of relapse of depression during the perinatal period. 17 Antepartum depression has been linked to negative health-related behaviors and adverse outcomes, including poor nutrition, increased substance use, inadequate prenatal care, preeclampsia, low birth weight, preterm delivery, postpartum depression, and suicide.…”
Section: Introductionmentioning
confidence: 99%